Strategi Penguasaan Literasi Digital dan Pemahaman Wacana - Muchtar, Mohamad Candra; R, Mantasiah; Juanda*, Juanda (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2025)
This article will present the understanding of digital discourse in the modern information age, focusing on the challenges faced by individuals in accessing and understanding multimodal texts on digital platforms such as social media and e-learning. The study identified patterns of understanding, including information fragmentation, difficulty verifying credibility, and challenges in understanding multimodal texts. The results of the study indicate the importance of individual comprehension strategies, such as cross-verification, additional reference searches, and the use of technology and collaboration features to overcome these obstacles. This study provides recommendations for educators and policymakers to design effective digital literacy programs, involving technologies such as Natural Language Processing (NLP) and data visualization to support discourse understanding, as well as encouraging the use of interactive and collaborative features in Ok Hb digital-based learning..Keywords: literacy; media; learningAbstrakArtikel ini akan memaparkan pemahaman wacana digital di era informasi modern, dengan fokus pada tantangan yang dihadapi individu dalam mengakses dan memahami teks multimodal di platform digital seperti media sosial dan e-learning. Penelitian mengidentifikasi pola-pola pemahaman, termasuk fragmentasi informasi, kesulitan memverifikasi kredibilitas, dan tantangan dalam memahami teks multimodal. Hasil penelitian menunjukkan pentingnya strategi pemahaman individu, seperti verifikasi silang, pencarian referensi tambahan, serta pemanfaatan fitur teknologi dan kolaborasi untuk mengatasi hambatan tersebut. Studi ini memberikan rekomendasi bagi pendidik dan pembuat kebijakan untuk merancang program literasi digital yang efektif, dengan melibatkan teknologi seperti Natural Language Processing (NLP) dan visualisasi data untuk mendukung pemahaman wacana, serta mendorong penggunaan fitur interaktif dan kolaboratif dalam Ok Hb pembelajaran berbasis digitalKatakunci: literasi; media; pembelajaran